Did the Exchange Rate Floor Prevent Deflation in the Czech Republic? - Caselli, Francesca (IMF Working Papers; Working Paper ;, 2017)
To fight deflationary pressures at the zero lower bound, in November 2013, the Czech National Bank (CNB) introduced a one-sided floor on the exchange rate, as an additional monetary policy instrument. This paper investigates the impact of the FX floor on inflation in the Czech Republic, by comparing actual inflation with counterfactuals in the absence of the exchange rate floor. Three different empirical strategies are implemented: an event study, difference-in-difference regressions and a synthetic control method. The empirical results provide evidence that the exchange rate floor was effective in fighting deflationary pressures and prevented inflation from going into negative territory. The magnitude of the effect ranges between 0.5 to 1.5 percentage points. The results are robust to different econometric specifications.